The potential of condensed waste water from air conditioning: \b office building - Faizatul Harlina Muhamad Shah (School of Environmental Engineering, University Malaysia Perlis, 2012)
This research is about the condensed waste water that flowing out from the air conditioning. There are three main objectives of this research. There are to determine the flow rate of the condensates that is flowing out from the air conditioning based on their capacity, to review the quality of condensates and then compare it with the The National Water Quality Standards (NWQS) and then to identify the potential of these condensates especially for the office buildings that can be reusable. After that, experiments will be conducted on the condensates water. The test that have be done are the pH test, the temperature test, turbidity test, the total of suspended solids (TSS), the total solids (TS), total phosphate (PO43-), nitrates (NO-3) and the Chemical Oxygen Demand (COD) test. From the results and analysis, these condensates passed all the parameters. The condensates particularly can use to prevent water wastage and reduce costs in the office building. Calculation for water savings also was shown. The condensates is slightly polluted and practically no treatment need and can directly used for watering plants and grass (avoid watering plants that can be eaten), gardens, washing vehicles, cleaning toilets and other daily uses. This condensate is not recommended for bathing and drinking. It is because depending on the age and condition of the unit of the air conditioning, any number of unhealthy materials could well be found in these condensates, such as lead, iron oxide or mercury. It also contains impurities in the air that came from the individual respiration in the room that may have a variety of diseases.